Platelet haemostatic function in psychiatric disorders: Effects of antidepressants and antipsychotic drugs. (17th November 2017) - Dietrich-Muszalska, Anna; Wachowicz, Barbara
Abstract: Objectives Platelets, the smallest anucleated blood cells, play an essential role in the first step of complex haemostatic process. This review presents the haemostatic function of blood platelets related to their activation in psychiatric disorders (schizophrenia, depression), the role of antipsychotic and antidepressant medication, and introduces the mechanisms by which activated platelets may be involved in the pathophysiology of these disorders.Methods Platelets are interesting and easily accessible blood cells to study biochemical pathways related to schizophrenia and other psychiatric disorders, and their complex activation process might be useful as a diagnostic peripheral marker for studying psychiatric disorders and haemostatic complications.Results The excessive activation of platelets observed in patients with depression and schizophrenia is involved in cardiovascular diseases, stroke and increased risk of thrombotic complications that may be major causes of morbidity and mortality of patients. The use of antidepressants or antipsychotic drugs in depression and schizophrenia treatment is often associated with haematological side effects such as bleeding, venous thromboembolism and impaired platelet function.Conclusions Understanding the role of platelet activation in psychiatric disorders such as schizophrenia or depression and medication may improve therapies in the future.